Presuppositions Used in Benjamin Netanyahu’s Speech at The Opening of The U.S. Embassy in Jerusalem - Sanjaya, Arik (Language Horizon: Journal of Language Studies, 2021)
Speech is a communication tool that occurs between speaker and audience. When delivering speech, a speaker tries to reach the audience through his words. Most of the time, a speaker delivers his speech to gain attention from the audience and persuade them to agree with what the speaker believes. This is the case with Benjamin Netanyahu who is an Israeli Politician and currently the Prime Minister of said country. He delivered his speech at the opening of new United States embassy in Jerusalem, which sparked the outrage of people around the world, as we know that Jerusalem belongs to Palestine but this action showed that the Israel government has already claimed Jerusalem as its capital. From the linguistics’ point of view, his speech is an interesting matter to be analyzed. Hence, this study aimed to analyze the types of presupposition used by Benjamin Netanyahu in his opening speech in Jerusalem and the purpose of using them. The fully transcribed speech is gained by downloading it from the internet. The result found that there are two kinds of presupposition used and each with pragmatic function that are emphasis, persuasive and euphemism. These presuppositions had purpose to express speaker’s attitude in a polite way and giving information to the audience.